Staff cooperation in the hospitality industry: seasonal slump to winter wonderland - Lieberman, Warren (Henry Stewart Talks, 2016)
The case study explores an upscale summer lodge which decided to tackle its yearly winter slump in occupancy by collecting input from hotel staff in all departments. Staff cooperation culminated in the creation of a special seasonal program which successfully raised revenue to record numbers during winter months.